Nano zinc – titanium – cerium Coating on BIS 2062 Boat building Carbon steel for Corrosion Protection - Ashraf, P. Muhamed; Anuradha, R. (Fishery Technology, 2020)
The corrosion inhibition ability of three nano oxides,zinc oxide, titanium oxide and cerium oxide coatingover BIS 2062 carbon steel was studied. Morphologyof the coating evaluated using SEM and AFMtechniques and it showed uniform coverage over thesurface and lower roughness than untreated steel.Electrochemical measurement in 3.5% NaCl showed3.5-fold increase in polarization resistance than baresteel. The electrochemical impedance spectroscopydata was exhibited comparable results as that oflinear polarization studies. The nano xode mixturehaving 0.01% each of zinc and titanium and 0.02%cerium showed adequate corrosion protection underthe marine environment.